1991
DOI: 10.1002/mrd.1080300105
|View full text |Cite
|
Sign up to set email alerts
|

Birth of lambs after in vitro maturation, fertilization, and coculture with oviductal cells

Abstract: Control ovine oocytes matured and fertilized in vitro were transferred to intermediate recipient ewes. After 5 days, 59% of eggs were recovered. Thirty-one (38%) reached morula/blastocyst stage. Twenty-one embryos at the morula or blastocyst stage were transferred to six recipient ewes, resulting in five pregnancies, of which four were maintained. Nine lambs were born (43%). In the experiment, 72 ooctyes matured and fertilized in vitro were cocultured for 5 days with sheep oviductal epithelial cells. Thirty-on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
4

Year Published

1992
1992
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 28 publications
0
6
0
4
Order By: Relevance
“…Most reports concerning in vitro production of embryos from in vivo ‐derived oocytes have been carried out using undefined maturation media, containing different combinations of sera and gonadotropins (Czlonkowska et al. 1991; Huneau et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most reports concerning in vitro production of embryos from in vivo ‐derived oocytes have been carried out using undefined maturation media, containing different combinations of sera and gonadotropins (Czlonkowska et al. 1991; Huneau et al.…”
Section: Discussionmentioning
confidence: 99%
“…Most reports concerning in vitro production of embryos from in vivo-derived oocytes have been carried out using undefined maturation media, containing different combinations of sera and gonadotropins (Czlonkowska et al 1991;Huneau et al 1994;Baldasarre et al 1996;Berlinguer et al 2004;Cox and Alfaro 2007;Morton et al 2008). To our knowledge, this is the first report in which IVP results of a defined (Cys + EGF) and an undefined (FSH + FF) maturation medium have been simultaneously compared using oocytes from three sources: FSH-stimulated live ewes, non-stimulated live ewes and abattoir-derived sheep ovaries.…”
Section: Discussionmentioning
confidence: 99%
“…The birth of the first IVP lambs in 1991 [36,37] and the first cloned animal (a lamb) by nuclear transfer in 1997 [38] are only two examples. Based on the International Embryo Transfer Society (IETS) data, a decade ago, Thibier [39] reported 6674 fresh and 2907 frozen sheep embryos transferred in the world in 2003, whereas, for the year 2012, Perry [40] referred 8124 fresh and 4120 frozen embryos, mainly represented by Australia, South America, and South Africa.…”
Section: Main Applications Of Sheep Cryopreserved Embryosmentioning
confidence: 99%
“…; Thompson ef al, 1989;McCaffrey et al, 1991;Prichard et al, 1992) could be overcome by temporarily incubating the embryos in oviducts from rabbits (Boland, 1984;Sirard et al, 1985), goats (Ryan et al, 1993) or sheep (Parrish et al, 1986;Crozet et al, 1987;Rexroad and Powell, 1988;Czlonkowska et al, 1991 ). Nevertheless, since Gandolfi and Moor (1987) demonstrated that a coculture with somatic cells could improve the development of ovine embryos, this system has been largely employed to obtain an adequate embryo development in ruminant species, after in vivo fertilization (IVOF) or IVF (Fukui et al, 1988;Powell, 1988/1991;Eyestone and First, 1989;Czlonkowska et al, 1991;Shamsuddin et al, 1993).…”
mentioning
confidence: 99%
“…Nevertheless, since Gandolfi and Moor (1987) demonstrated that a coculture with somatic cells could improve the development of ovine embryos, this system has been largely employed to obtain an adequate embryo development in ruminant species, after in vivo fertilization (IVOF) or IVF (Fukui et al, 1988;Powell, 1988/1991;Eyestone and First, 1989;Czlonkowska et al, 1991;Shamsuddin et al, 1993).…”
mentioning
confidence: 99%